Implementation Of Sharia Principles In Investment Management In Islamic Banking - Ainun Ara As’syahra; Dwi Magfiratul Rahma (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study evaluates the operationalization of Islamic jurisprudence within corporate wealth management structures to determine how modern portfolios align with normative regulatory frameworks. Employing a non empirical qualitative design driven by a systematic content analysis framework, the research examines the structural integration of normative theology and macroeconomic architectures. The analytical model decodes foundational texts, statutory banking laws, and national religious fatwas through systematic data reduction, thematic categorization, and conceptual synthesis. The findings indicate that the execution of trust partnerships, joint equity pooling, and asset backed exchange structures naturally mitigates moral hazard while optimizing liquidity distribution. Furthermore, combining international governance benchmarks with independent sharia supervisory controls shields institutional frameworks from systemic market volatility and asymmetric information gaps. The structural synthesis demonstrates that banking resilience depends heavily on anchoring transaction instruments to tangible real sector ventures rather than speculative metrics. Ultimately, this integration establishes a disciplined investment ecosystem that maximizes commercial returns while maintaining absolute regulatory compliance.